RELATIONSHIP BETWEEN THE ANGLE OF INCLINATION OF THE MAXIMUM INCLINATION TO THE SOFT TISSUE OF THE FACIAL IN BALINESE WOMEN USING THE HOLDAWAY METHOD: HUBUNGAN ANTARA SUDUT INKLINASI INSISIVUS RAHANG ATAS TERHADAP KECEMBUNGAN JARINGAN LUNAK WAJAH PADA PEREMPUAN SUKU BALI DENGAN METODE HOLDAWAY - Norman Hidajah; Dwis Syahrul; Virtika Ayu Ketut (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Disharmony between tooth position, jaw relation and facial soft tissue has a significant effect on facial appearance. Anatomical facial appearance is determined by the lower third of the face, especially the position of the lips and related parts which are affected by the inclination of the anterior teeth. The purpose of this study was to determine whether there was a correlation between the angle of inclination of the maxillary incisors and the convexity of facial soft tissue in Balinese women using the Holdaway method. Materials and Method: This type of research was analytic observational with a cross sectional approach. This study used a sample of 31 lateral cephalometric photographs of Balinese females for tracing. Samples were taken by means of purposive sampling, based on specified criteria. Results and discussion: Pearson correlation analysis showed that the relationship between the angle of inclination of the upper incisors was significant. Conclusion: Based on this study, it can be concluded that there was a correlation between maxillary incisor inclination angle on the facial soft tissue convexity in Balinese females using the Holdaway method.